2022
DOI: 10.1039/d1tc04248c
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional polymer memristor based on conformational changes with tunable resistive switching behaviours

Abstract: A resistive switching memory device based on a 2DPTPAK+TAPB film with the conformational change mechanism was prepared and the memory behaviors can be adjusted by the degree of conformational changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…3a) suggested the presence of unreacted carbonyl groups in the poly-TT 2DP film. 12,40 Raman spectra (see ESI, † Fig. S5) showed a new band at 1587 cm À1 after the Schiff base condensation reaction, which could be ascribed to the imine stretching mode 40 and thus confirmed the formation of imine bonds in the poly-TT 2DP film.…”
Section: Structural Characterization and Stability Of The Poly-tt 2dp...mentioning
confidence: 78%
See 1 more Smart Citation
“…3a) suggested the presence of unreacted carbonyl groups in the poly-TT 2DP film. 12,40 Raman spectra (see ESI, † Fig. S5) showed a new band at 1587 cm À1 after the Schiff base condensation reaction, which could be ascribed to the imine stretching mode 40 and thus confirmed the formation of imine bonds in the poly-TT 2DP film.…”
Section: Structural Characterization and Stability Of The Poly-tt 2dp...mentioning
confidence: 78%
“…12,40 Raman spectra (see ESI, † Fig. S5) showed a new band at 1587 cm À1 after the Schiff base condensation reaction, which could be ascribed to the imine stretching mode 40 and thus confirmed the formation of imine bonds in the poly-TT 2DP film. As a result of the covalently linked structure, the poly-TT 2DP film exhibited high thermal stability and high solvent tolerance.…”
Section: Structural Characterization and Stability Of The Poly-tt 2dp...mentioning
confidence: 78%
“…During the past decade, a large number of studies have been conducted on the preparation methods of memristive materials, tunable performance, and device manufacturing. To date, a wide range of inorganic and organic memristive materials have been intensively studied, including inorganic oxides, [ 5 ] phase‐change materials, [ 6 ] organic small molecules, [ 4b,7 ] polymers, [ 8 ] organic nanocrystals, [ 9 ] semiconductor quantum dots (SQDs), [ 10 ] van der Waals and 2D materials, [ 11 ] novel carbon materials, [ 12 ] biomaterials, [ 13 ] MXenes, [ 14 ] ferroelectric materials, [ 15 ] perovskites, [ 16 ] as well as their hybrid composites. [ 17 ] For organic memristive materials, one of the challenges is their insufficient stability and low tolerance to ambient conditions, whereas inorganic memristive materials are limited by their poor flexibility and tunability.…”
Section: Introductionmentioning
confidence: 99%
“…Conformation change-induced resistive switching could also be achieved in COF materials. Song et al 98 reported tunable resistive switching behaviors in a memory device based on carbazole-containing 2D polymer, where the carbazole groups are linked to the polymer skeleton through flexible C−O single bonds (Figure 4g). In HRS, the carbazole groups distribute in the polymer with random orientation, leading to low charge transport efficiency.…”
mentioning
confidence: 99%
“…Conformational Change . Some polymers with planar-conjugated functional groups can conduct conformational transformation with external electrical stimulus, leading to the conductivity variation. For instance, the electron-donating carbazole groups are prone to configuration with varying degrees of π–π stacking conformation, regulating the density of the delocalized electrons (Figure e). To determine conformational change, in addition to computational simulation, several experimental studies have been carried out, such as TEM, scanning tunneling microscope (STM), X-ray diffraction (XRD), and UV spectrum analysis. …”
mentioning
confidence: 99%